STUDI KASUS TINGKAT MOTIVASI SISWA SMK TERHADAP PEMBELAJARAN IPA DI SEKOLAH - Sanimah Sanimah; Sri Wahyuni; Imelda Wardani Lambe (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2021)
Natural Science subject in Vocational High School is included in the adaptive subject group, a subject that act as a support for the achievement of competency skills or productive subjects. This case study research aims to obtain information about the level of student motivation in learning science at SMK. This research involved 30 students of the Motorcycle Engineering expertise program at one of SMK in Stabat District. The data was collected through a student questionnaire. The results showed that science learning supported the mastery of skill competencies so that student learning motivation was high. From the results of data processing, the percentage of students' motivation level in science learning reached 82.9%. This means that students' motivation in learning science is included in the very good category. Based on the findings, it is necessary to follow up the development of appropriate learning methods to integrate science skills with productive subjects to improve student learning outcomes.